Effect of land-use and land-cover change on mangrove blue carbon: A systematic review - Sasmito, S.D.; Taillardat, P.; Clendenning, J.; Cameron, C.; Friess, D.A.; Murdiyarso, D.; Hutley, L.B. (Wiley, 2019)
Mangroves shift from carbon sinks to sources when affected by anthropogenic land‐use and land‐cover change (LULCC). Yet, the magnitude and temporal scale of these impacts are largely unknown. We undertook a systematic review to examine the influence of LULCC on mangrove carbon stocks and soil greenhouse gas (GHG) effluxes. A search of 478 data points from the peer‐reviewed literature revealed a substantial reduction of biomass (82% ± 35%) and soil (54% ± 13%) carbon stocks due to LULCC. The relative loss depended on LULCC type, time since LULCC and geographical and climatic conditions of sites. We also observed that the loss of soil carbon stocks was linked to the decreased soil carbon content and increased soil bulk density over the first 100 cm depth. We found no significant effect of LULCC on soil GHG effluxes. Regeneration efforts (i.e. restoration, rehabilitation and afforestation) led to biomass recovery after ~40 years. However, we found no clear patterns of mangrove soil carbon stock re‐establishment following biomass recovery. Our findings suggest that regeneration may help restore carbon stocks back to pre‐disturbed levels over decadal to century time scales only, with a faster rate for biomass recovery than for soil carbon stocks. Therefore, improved mangrove ecosystem management by preventing further LULCC and promoting rehabilitation is fundamental for effective climate change mitigation policy.